Community assessment of NGO housing delivery: lessons from Port Vila, Vanuatu. Issue 4 (19th May 2019) - Strychar, Lisa; Day, Jennifer
ABSTRACT: This article reports on a 2016 field-based multiple case study of three communities in peri-urban Port Vila, Vanuatu. It offers robust empirical evidence that participatory planning, partnerships, and programme evaluation, as espoused in the literature from the last two decades and readdressed in Habitat III Conference on Housing and Sustainable Urban Development, is not regularly occurring in aid-based housing programmes. The study identifies that in sacrificing consultation – community cohesion, capacity building, resiliency, and innovation, are also sacrificed. This research differs from peer literature by employing an inductive and underutilised methodology, storytelling, and by focusing on an at-risk country which receives little academic, NGO, or development attention.